The Impact of Cooking on Antioxidant and Enzyme Activities in Ruichang Yam Polyphenols - Haoping Liu; Hua Zhang; Mengting Geng; Dingxin Shi; Dongsheng Liu; Yanxiao Jiao; Zhiqiang Lei; You Peng (Foods)
In this study, the total polyphenol content (TPC), total flavonoid content (TFC), and biological activity of yam polyphenols (including free phenolics, conjugated phenolics, and bound phenolics) were investigated during home cooking. Polyphenol components were preliminary detected in raw yam by HPLC, including 2, 4-dihydroxybenzoic acid, syringic acid, vanillic acid, 4-coumaric acid, and sinapic acid. TPC and TFC of soluble conjugated polyphenols were the main phenolic compounds in Ruichang yam. Compared with uncooked yam, cooking times of 80 min and 40 min increased the TPC and TFC of multiple types of polyphenols, while cooking reduced the TPC and TFC of AHP (acid-hydrolyzed soluble conjugated polyphenols). All yam polyphenols exhibited good α-Glucosidase inhibitory activity; α-Glucosidase inhibitory activity was significantly higher for a cooking time of 120 min. Only some types of polyphenols had lower pancreatic lipase half-inhibition concentrations than orlistat when cooked. The pancreatic lipase of FPs (free polyphenols), BHPs (alkali-hydrolyzed soluble conjugated polyphenols), and ABPs (acid-hydrolyzed insoluble bound polyphenols) was the stronges when cooking for 80 min, and the pancreatic lipase inhibitory activity of AHPs and BBPs (alkali-hydrolyzed insoluble bound polyphenols) was strongest when cooking for 40 min. Pearson’s correlation coefficient analysis revealed that the TPC was positively correlated with the TFC, the IC50 value of α-Glucosidase was negatively correlated with the IC50 value of pancreatic lipase, and redox activity was positively correlated with the TPC and TFC, respectively.